Intellectual Property - Gamboa Vilela, Patricia Victoria (2013)
According to the World Intellectual Property Organization (WIPO), intellectual property refers to creations of the mind: inventions, literary and artistic works, marks, and other distinctive signs, as well as drawings and designs used in commerce. Hence, Intellectual Property Law is the area of Law called upon to protect the creations of the mind and is divided into two branches: Copyright and Intellectual Property.